LEGAL PROTECTION AGAINST A BOND INVESTOR ACCORDING TO THE DIGNIFIED JUSTICE - Tommy Leonard; Elvira Fitriyani Pakpahan; Heriyanti Heriyanti; Azharuddin Azharuddin (Faculty of Law, Universitas Sebelas Maret, 2020)
The defaulted cases that occurred at PT. Mobile-8 Telecom Tbk., Bakrie Telecom, PT. Berlian Laju Tanker is very detrimental to bondholder investors. This is the problem that is happening in the Indonesian economy and becomes serious since it can reduce the wheels of the economy, especially for the capital market. The purpose of this research is to protect investor-based bonds with dignified justice according to Teguh Prasetyo's dignified justice theory. The research method used is empirical or non-doctrinal. The results of the research stated that legal protections based on fairness are not only given to bond investors but issuers and trustees